Design and Build a Web Service for Mobile Ecotourism in the City of Bogor Using the Rest . Method - Aliwafa, Muhamad; Hidayat A, Safaruddin; Fajar Kusumah, Fitrah Satrya (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
The tourism sector is one sector that plays an important role in economic growth in Indonesia. Improving services to tourists when traveling with the use of technology is one of the efforts to support the development of tourism in Indonesia. The eCotourism application is a mobile-based application that serves to provide services to tourists such as providing information about tourist locations, lodging locations, culinary locations, and souvenir locations. In addition, in the eCotourism application, several functions can provide services to tourists while traveling, such as a digital guide system using a QR code. However, in the development process, a system is needed that can provide services to the functions and data that exist in the eCotourism application. In this study, the system that will be created is a web service for eCotourism applications where the web service will function as a bridge for the process of exchanging data between eCotourism applications and the database. In addition, the web service that is built is also able to support the functions that exist in the eCotourism application and is multi-platform so that it can be accessed by various application platforms. The architecture used in making the web service is REST (Representational State Transfer Protocol) architecture which uses the HTTP method to process data exchange via URL (Uniform Resource Locator). Making a web service can help eCotourism applications in providing services to tourists when traveling by providing data and existing functions. In addition, making this web service is also able to integrate eCotourism applications with other applications.